Measurement of the information system project success of the higher education institutions in Indonesia: A pilot study - Subiyakto, A'ang; Ahlan, Abdul Rahman; Kartiwi, Mira; Jaya Putra, Sopiyanshah (Inderscience Pusblishers, 2016)
This paper presents a pilot study to validate quantitatively an information system (IS) project success model. In terms of its continual research, the model was evaluated qualitatively using focus group study (FGS) conducted earlier in the research. This study was also aimed to explain an IS project success performance and its factors that affect the project implementation in the sampled institution. Despite that the findings and its recommendations can only be considered in the context of the pilot study, this research had highlighted the complementary, completeness, and comprehensiveness of the model validation through mixed-methods approach. Such findings had become the main contribution of this study, among others, that is to fill the gap in the literature of the lack of comprehensive detail of model validation through mixed-methods.